The nature of the band gap of GeSn alloys - Schulz, Stefan; Broderick, Christopher A.; OrHalloran, Edmond J.; OrReilly, Eoin P. (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
We present a detailed analysis of the electronic structure of GeSn alloys using density functional theory. Special attention is paid to Sn-induced conduction band mixing effects. Our calculations indicate a continuous evolution from an indirect to a direct band gap material with increasing Sn content. This finding is in stark contrast to the literature perception of a sharp transition at a fixed critical Sn composition. Finally, we discuss and present initial results on how the density functional data is used to establish semi-empirical tight-binding models.